Issuers, Use of Proceeds, and the Cost of Capital for the Issuance of Green Bonds: evidence from the market in China - Zhang, Hui-Jun (2022)
This paper is focused on green bonds issued in the Chinese market from 2016 to 2020. The difference of the cost of capital for issuing green bonds is found between these issuers: commercial banks and industrial companies; State-Owned Enterprises and non-State-Owned Enterprises. The paper also finds the different cost of capital for varying degrees of green use of proceeds. According to the empirical analysis results, the suggestions about the regulation of the Chinese green bonds market are put forward.